Studies in Area Linguistics - Kurath, Hans (Indiana University Press, 1972)
A broad survey of the techniques and results of research in linguistic geography, Studies in Area Linguistics presents in condensed form the major aspects of linguistic area studies in the Western world. It discusses the use of "indicative" heteroglosses, the modification of transplanted languages, and the influence of foreign elements on a native language. It concludes with a major chapter on social dialectology (the social aspect of linguistics) which discusses urban and rural speech, and variations within urban areas; black speech in Washington, Tennessee and Chicago; and Mexican-American speech.